(untitled) (Bangladesh Journal of Pharmacology, 2011)
Five NH-derivatives of ciprofloxacin (2-6) have been prepared by acetylation/benzoylation on ciprofloxacin (1) in order to carry out screening for antibacterial activities on some Gram-positive and Gram-negative bacteria. The antifungal activity of these compounds has also been made against Candida albicans. All of the derivatives have shown enhanced activities against Gram-negatives bacteria than parent antibiotic, ciprofloxacin among which compounds 2 and 6 are the most potent agents. Regarding the antifungal activity all of the compounds have shown highest activity than ciprofloxacin. All the compounds have been characterized with spectral analysis.